Replicating organizational knowledge: principles or templates? - Charles Baden-Fuller; Sidney G. Winter (Max Planck Institute of Economics, 2005)
We discuss how firms can replicate practices and knowledge embedded in practices by following principles, with no direct reference to an extant working example (template). Definitions are provided for the key concepts of templates, principles, and background knowledge. We address the challenges of providing operational measures for successful replication, and for comparing the efficacy of principles and templates. By using two longitudinal case studies of replication across the units of two multi-unit organizations, we support the central claim that in certain circumstances replication by principles can be as speedy and cost effective as replication with templates, and deliver results of comparable quality. The principle contingencies affecting the relative performance of the two methods are identified. We also point out that replication efforts can be a source or incubator, as well as an application area, for dynamic capabilities in an organization. We briefly suggest what the results may mean for theories of knowledge-based competition.
Keywords: 330; Replication; Principles; Templates; Capability Development